Identification and characterization of near‐fatal asthma phenotypes by cluster analysis. Issue 9 (9th June 2015) - Serrano‐Pariente, J.; Rodrigo, G.; Fiz, J. A.; Crespo, A.; Plaza, V.; the High Risk Asthma Research Group
Abstract Background Near‐fatal asthma (NFA) is a heterogeneous clinical entity and several profiles of patients have been described according to different clinical, pathophysiological and histological features. However, there are no previous studies that identify in a unbiased way – using statistical methods such as clusters analysis – different phenotypes of NFA. Therefore, the aim of the present study was to identify and to characterize phenotypes of near fatal asthma using a cluster analysis. Methods Over a period of 2 years, 33 Spanish hospitals enrolled 179 asthmatics admitted for an episode of NFA. A cluster analysis using two‐steps algorithm was performed from data of 84 of these cases. Results The analysis defined three clusters of patients with NFA: cluster 1, the largest, including older patients with clinical and therapeutic criteria of severe asthma; cluster 2, with an high proportion of respiratory arrest (68%), impaired conciousness level (82%) and mechanical ventilation (93%); and cluster 3, which included younger patients, characterized by an insufficient anti‐inflammatory treatment and frequent sensitization to Alternaria alternata and soybean. Conclusions These results identify specific asthma phenotypes involved in NFA, confirming in part previous findings observed in studies with a clinical approach. The identification of patients with a specific NFA phenotype could suggest interventions to prevent future severe asthma exacerbations.